Clinicopathological and Molecular Features of Colorectal Cancer Patients With Mucinous and Non-Mucinous Adenocarcinoma - Lan, Yuan-Tzu; Chang, Shih-Ching; Lin, Pei-Ching; Lin, Chun-Chi; Lin, Hung-Hsin; Huang, Shen-Chieh; Lin, Chien-Hsing; Liang, Wen-Yi; Chen, Wei-Shone; Jiang, Jeng-Kai; Lin, Jen-Kou; Yang, Shung-Haur (Frontiers in Oncology, 2021)
Background The prognosis of mucinous adenocarcinoma (MAC) and non-mucinous adenocarcinoma (NMAC) in colorectal cancer (CRC) is controversial, and the molecular differences between them are unclear. Methods Between 2000 and 2010, a total of 1,483 CRC patients were included. Among them, 73 patients (4.9%) were diagnosed with MAC. The clinicopathological features and genetic alterations were compared between MAC and NMAC. Results After propensity score matching to balance age and sex between MAC and NMAC patients, 292 CRC patients (73 MAC and 219 NMAC) were enrolled in the analysis at a 1:3 ratio. In right-sided colon cancer, patients with MAC were more likely to have Borrmann types 3 and 4 tumors, poor differentiation, and advanced T category and tumor, node, metastasis (TNM) stage, chemotherapy, and a similar 5-year overall survival (OS) rate compared with patients with NMAC. In left-sided colon cancer and rectal cancer, patients with MAC were more likely to have Borrmann types 3 and 4 tumors, poor differentiation, lymphovascular invasion, advanced T and N categories and TNM stages, chemotherapy, and a worse 5-year OS rate than patients with NMAC. Regarding genetic alterations, for NMAC, right-sided colon cancer had more BRAF mutations than left-sided colon cancer and rectal cancer. For MAC, right-sided colon cancer was associated with more microsatellite instability-high tumors and more AKT1 mutations than left-sided colon cancer and rectal cancer. Conclusion The genetic alterations are distinct between MAC and NMAC in CRC. Tumor location may have an impact on genetic alterations and patient prognosis in MAC and NMAC.